PP.39.04: REVASCULARISATION OF HIGH-GRADE BILATERAL RENAL ARTERY STENOSIS. (June 2015) - Schulte-Kemna, L.; Seitz, K.H.; Büttner, S.; Reimer, P.; Krämer, B.K.; Hausberg, M.
Abstract : Objective: The appropriate strategy for atherosclerotic renal artery stenosis remains controversial. Randomized controlled trials did not show a benefit of revascularization as compared with conservative therapy alone, however due to potential issues concerning study design these trials continue to be debated. Our retrospective case-control study reviews the effects of revascularisation of high-grade bilateral renal artery stenosis on renal function, hypertension and the occurence of cardiovascular events. Design and method: At Karlsruhe General Hospital, Germany, 52 revascularisations for high-grade bilateral renal artery stenosis were performed between 2006 and 2011, 33 patients undergoing conservative treatment served as control group. High-grade renal artery stenosis was assessed by colour-coded duplex ultrasound. The evolution of antihypertensive medication, renal function, hypertension, the occurence of cardiovascular events and complications were compared between the two groups. Results: The groups did not differ significantly in terms of age, sex, kidney function, comorbidities, cardiovascular risk factors and average follow-up time of 34.5 months. At baseline, patients in the revascularisation group took significantly more antihypertensive drugs than patients in the medical group (3.9 versus 3.0, p < 0.05). Following revascularisation, the number of antihypertensive drugs was reduced by 0.76, while it increased by 0.47 in the conservative group (p < 0.0001). Patients in the conservative group were hospitalized more frequently for heart failure (38.5% versus 13.6%, p = 0.016). More patients in the conservative group died during follow-up (39.4% versus 10%, p = 0.041). Serum creatinine tended to fall from 2.2 mg/dl to 1.8 mg/dl after intervention and did not change significantly in the conservative group(2 mg/dl at baseline and the end of follow-up). Blood pressure changed from 154/78 mmHg to 140/73 mmHg after intervention and from 159/74 mmHg to 150/80 mmHg in the conservative group. Conclusions: The results of this case-control study, including severely morbid patients – generally excluded in prospective randomized controlled studies – suggest a benefit of revascularisation over medical therapy alone in patients with high-grade bilateral renal artery stenosis. Our study warrants further prospective investigations, particularly since the published randomized studies have resulted in a progressive neglect of diagnosis and treatment of renal artery stenosis due to apparent lack of therapeutic consequences.